Handbook of restorative justice - Johnstone, Gerry; Van Ness, Daniel W. 1949- (Gale virtual reference library, 2007)
Discusses the key concepts and principles of restorative justice; explains how the campaign for restorative justice arose and developed into an influential social movement; describes the variety of restorative justice practices; and identifies and examines key issues within the restorative justice movement.